KOMUNIKASI ANTARPRIBADI SEBAGAI SOLUSI KONFLIK ANTARA ORANG TUA DAN ANAK - Uun Machsunah (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2019)
A harmonious relationship between parents and children is ideal in a family. If this happens of course because among the members in it do intense and quality interpersonal communication so the results are positive. The family is a pillar that builds the mentality of children, in their journey they are expected to grow and develop healthily so that when interacting with the environment in the community they do not do destructive actions. But communication that occurs in the family is not always smooth. This is because between parents and children are often not in line in thinking. Parents feel they have an obligation to regulate the lives of their children so that their future is better, on the contrary the children feel mature and have their own desires so that they are constrained by the rules of their parents. If interpersonal communication is not carried out in a healthy manner as a result there will be conflict between them. Children who often have unresolved conflicts with their parents are at high risk for delinquency. The existence of conflict in the family makes children lose their personal experience, which is full of love and shelter. Conflict occurs when both parties experience disagreement about something. The solution is when that happens, conflict resolution expertise needs to overcome differences and maintain positive relationships. When communication and conflict solutions are seen as a problem, we must refer to the problem in the relationship between individuals. The ability and strategy of building and developing interpersonal communication to resolve conflicts are important for all stages of human development, because they can lead to productive and harmonious relationships. Keywords: communication, parents, children, interpersonal communication, solutions